(untitled) (Nexo Revista Científica, 2020)
An analysis of the Cuba`s seismic activity is presented. This island has a Mmax of 7.7 that is associated to the vicinity of Cabo Cruz, with the Oriente fault. The greatest seismic hazard is in the city of Santiago de Cuba. The seismicity of neighboring islands has affected Cuba, and they have a higher level of activity, including the tsunami genetic. A diagnosis of strong earthquakes is given.